2009
DOI: 10.1080/00016480802495404
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical instrument improving rehabilitation of olfaction with the Nasal Airflow-Inducing Maneuver in Swedish laryngectomized patients

Abstract: According to the NAIM evaluation protocol patients significantly improved their execution of the NAIM technique over time and these improvements were associated with improvements in olfactory acuity (SOIT). Using the protocol important key variables for improvement of the NAIM technique were identified. The inter- and intra-rater reliability for the NAIM evaluation protocol was moderate to good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…[76] Efficacy of converting non-smellers to smellers post-TL has been shown, both in the short-and long-term, with success rates ranging from 46% to 88%. [1,12,77] Methods of treatment delivery and intensity have varied in the literature [ Table 4], [1,11,12,14,[77][78][79][80] but there is a general consensus that although treatment can be effective with a single Figure 1: Schematic drawing of a larynx bypass used to bypass the upper airways to enable orthonasal airflow Figure 2: Schematic drawing of the Nasal Airflow Inducing Maneuver intervention, [1,11,80] further clinician-guided sessions lead to continued and more expeditious improvement in olfactory ability. [14] Research has also established the benefits of utilizing biofeedback to facilitate NAIM training.…”
Section: Intervention To Enhance Olfactory Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[76] Efficacy of converting non-smellers to smellers post-TL has been shown, both in the short-and long-term, with success rates ranging from 46% to 88%. [1,12,77] Methods of treatment delivery and intensity have varied in the literature [ Table 4], [1,11,12,14,[77][78][79][80] but there is a general consensus that although treatment can be effective with a single Figure 1: Schematic drawing of a larynx bypass used to bypass the upper airways to enable orthonasal airflow Figure 2: Schematic drawing of the Nasal Airflow Inducing Maneuver intervention, [1,11,80] further clinician-guided sessions lead to continued and more expeditious improvement in olfactory ability. [14] Research has also established the benefits of utilizing biofeedback to facilitate NAIM training.…”
Section: Intervention To Enhance Olfactory Performancementioning
confidence: 99%
“…Although research has shown that patients can restore sense of smell years after TL using this technique, [1,11,12,78,79] it is preferable to determine patient suitability for NAIM training during preoperative assessment and counseling. [73] Patients may be unsuitable to undergo olfactory rehabilitation with NAIM if they were anosmic prior to TL, or those with anatomical changes that influence adequate orofacial movement to perform the maneuver post-TL.…”
Section: Intervention To Enhance Olfactory Performancementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Olfactory epithelial damage is also reported to be a consequence of laryngectomy, 1,3,6,7,9 although this is controversial. 10 Much effort has been put into overcoming this problem, 4,5,11 but most attempts have been unsuccessful. 12 In 2000, Hilgers et al reported a nasal airflow-inducing manoeuvre that aimed to solve this problem, and had a noticeable success rate.…”
Section: Introductionmentioning
confidence: 99%
“…9 Since then, other researchers have adopted the nasal airflow-inducing manoeuvre, with varying success. 11,[13][14][15] Despite the efficiency of this technique in improving patient quality of life after laryngectomy, the effect of different nasal variables on the outcome of this procedure and on outcome stability are unclear. 16 However, nasal endoscopy findings such as non-use rhinitis can be considered probable effective factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation